Economic analysis of liability rules - Jain, Satish Kumar (Springer India Imprint: Springer, 2015)
This book focuses on the analysis of liability rules of tort law from an efficiency perspective, presenting a comprehensive analysis of these rules in a self-contained and rigorous yet accessible manner. It establishes general results on the efficiency of liability rules, including complete characterizations of efficient liability rules and efficient incremental liability rules. The book also establishes that the untaken precaution approach and decoupled liability are incompatible with efficiency. The economic analysis of tort law has established that for efficiency it is necessary that each party to the interaction must be made to internalize the harm resulting from the interaction. The characterization and impossibility theorems presented in this book establish that, in addition to internalization of the harm by each party, there are two additional requirements for efficiency. Firstly, rules must be immune from strategic manipulation. Secondly, rules must entail closure with respect to the parties involved in the interaction giving rise to the negative externality, i.e., the liability must not be decoupled.